The hidden oracle - Riordan, Rick (New York : Disney-Hyperion, 2016)
After angering his father Zeus, the god Apollo is cast down from Olympus. He must learn to survive in the modern world until he can somehow find a way to regain Zeus's favor.
Keywords: Apollo -- (Deity) -- Juvenile fiction; Gods, Greek -- Juvenile fiction; Mythology, Greek -- Juvenile fiction